Secondary structure of component 8c-1 of alpha-keratin. An analysis of the amino acid sequence. - Dowling, L M (1986)
The amino acid sequence of component 8c-1 from alpha-keratin was analysed by using secondary-structure prediction techniques, homology search methods, fast Fourier-transform techniques to detect regularities in the linear disposition of amino acids, interaction counts to assess possible modes of chain aggregation and assessment of hydrophilicity distribution. The analyses show the following. The molecule has two lengths of coiled-coil structure, each about 20 nm long, one from residues 56-202 with a discontinuity from about residue 91 to residue 101, and the other from residues 219-366 with discontinuities from about residue 238 to residue 245 and at about residue 306. The acidic and basic residues in the coiled-coil segment between residues 102 and 202 show a 9,4-residue structural period in their linear disposition, whereas between residues 246 and 366 a period of 9.9 residues is observed in the positioning of ionic residues. Acidic and basic residues are out of phase by 180 degrees. Similar repeats occur in corresponding regions of other intermediate-filament proteins. The overall mean values for the repeats are 9.55 residues in the N-terminal region and 9.85 residues in the C-terminal region. The regions at each end of the protein chain (residues 1-55 and 367-412) are not alpha-helical and contain many potential beta-bends. The regions specified in have a significant degree of homology mainly due to a semi-regular disposition of proline and half-cystine residues on a three-residue grid; this is especially apparent in the C-terminal segment, in which short (Pro-Cys-Xaa)n regions occur. The coiled-coil segments of component 8c-1 bear a striking similarity to corresponding segments of other intermediate-filament proteins as regards sequence homology, structural periodicity of ionic residues and secondary/tertiary-structure predictions. The assessments of the probabilities that these homologies occurred by chance indicate that there are two populations of keratin filament proteins. The non-coiled-coil regions at each end of the chain are less hydrophilic than the coiled-coil regions. Ionic interactions between the heptad regions of components 8c-1 and 7c from the microfibrils of alpha-keratin are optimized when a coiled-coil structure is formed with the heptad regions of the constituent chains both parallel and in register.